Numerical modelling for assessment of rainfall-induced slope failure - Tan, Brena Li En (Nanyang Technological University, 2020)
As a result of climate change, extreme weather events have been becoming more prevalent in recent years. Rainfall has also become unpredictable, resulting in rainfalls that are more intense and frequent. This will lead to a further increase in rainfall-induced slope failures which can cause detrimental consequences to the environment and society. To prevent such consequences, it is essential to study the characteristics and properties of residual soil slope and its factor of safety. Hence, the objective of this project is to investigate the saturated and unsaturated soil properties together with the factor of safety of two residual soil slopes from Holland Road and NTU. Soil-water characteristic curve (SWCC) tests were performed in the laboratory to obtain properties of the soil from both slopes. Laboratory results were then incorporated in Geostudio for numerical analyses for comparison with field instrumentation data. The resulting factor of safety values were then compared with those from an existing slope susceptibility map. The SWCC test results from Holland Road and NTU were within the range of SWCC parameters for residual soil from Jurong formation. The outcomes of the investigation of the factor of safety for both slopes from the numerical analysis were consistently higher as compared to that from the slope susceptibility map. This could be due to the different analysis method used in generating the factor of safety values. A correction factor could be incorporated in future research to account for the difference in the method of analysis.